Histostructure of the gray matter of the spinal cord in cattle (Bos Taurus) - I. M. Sokulskyi; L. P. Goralskyi; N. L. Kolesnik; O. F. Dunaievska; N. L. Radzikhovsky (Ukrainian Journal of Veterinary and Agricultural Sciences, 2021)
The scientific article presents the results of investigating the spinal cord`s morphology of a domestic bull (Bos Taurus). Data on the histo- and cytostructure of the spinal cord are given according to the results of histological, neurohistological, and morphometric studies. For their implementation, the selected material (spinal cord n = 8) was subjected to fixation in 10–12 % neutral formalin solution, followed by pouring into paraffin. Histological sections were made from paraffin blocks on a sliding microtome MS-2 with a thickness of not more than ten μm. Staining of sections with hematoxylin and eosin, according to Van Gieson's methods, as well as neuro-histological methods of impregnation of nerve tissue with silver nitrate according to the Bilshovskym-Gross method, was used for the morphometric studies, investigating the morphology of the cell, conducting and obtaining the review histological preparations. The histostructure of the spinal cord, the localization of neurons in the gray matter, and morphometric studies of structural elements were examined on histological specimens by light microscopy. The entire experimental part of the research was conducted following the requirements of the international principles of the "European Convention for the Protection of Vertebrate Animals for Experimental and Other Scientific Purposes" (Strasbourg, 1986). The spinal cord, medulla spinalis, an organ of the central nervous system of vertebrates, is located in the spinal canal. The spinal cord is protected externally by soft, arachnoid, and hard meninges. The space between the membranes and the spinal canal is filled with cerebrospinal fluid. It is well known that groups of multipolar nerve cells with the same functional value form the nuclei of the gray matter of the spinal cord. According to the results of our histological studies, a pronounced differentiation of nerve cells, which have different shapes and sizes. Among them are large, medium, and small nerve cells. The shape of nerve cells is different, which, in turn, depends on their location in certain areas of the gray matter of the spinal cord and the size of the cell. In general, there are multifaceted, stellate, spindle-shaped, elongated, rounded, and oval neurons. Small nerve cells have an oval or round, less often – irregularly rounded shape, medium – round, oval, spindle-shaped. Large nerve cells are dominated by a multifaceted shape with distinct processes. The nuclei of large nerve cells, in most cases, have a rounded shape, less often – oval, mostly in the center of the cells, seldom – eccentrically. According to the results of morphological studies, it is noted that the neurons of the gray matter of the spinal cord have different shapes and sizes. Consequently, in the gray matter, small cells are the highest quantity (47.91 ± 0.32 %) of the total number of nerve cells. The second place is occupied by average neurons (33.70 ± 0.46 %). The large cells are detected in the smallest amount (18.37 ± 0.50 %).